Design and Implementation of Solar Cell Cleaning Control System - Ajaweed, Mazin N.; Muhssin, Mazin T. Muhssin; A. Al-Mashhadani, Abduallah (Journal of Engineering and Sustainable Development, 2024)
The Republic of Iraq, similar to other Gulf countries is affected by the swings in oil costs, which motivates the policy makers to start thinking about integrating renewable energy such as PV power plants into the grid. This study is conducted to provide a solution for the accumulation of dust and dirt on the PV panels which is a problem of national and international significance. The accumulated dust on the panels of solar cells reduces the applied radiation of sunlight and reduces the efficiency of the solar cells. In this paper, a remote cleaning control system is designed and implemented practically to maintain the panels’ cleanliness. The control system is implemented on the real solar panel at different times throughout the day and is characterized by a lightweight and tight structure. The results show that there is a noticeable efficiency improvement for the solar panel output when it is cleaned in comparison to when it is heavily and medium dusted. After cleaning the panel, the average dissipated power with different tilt angles is increased by almost 1.75W when power measurement is collected at 9 am and 1.85W when measurement is collected at noon.